Quantitative analysis of serum chemokines associated with treatment failure of direct-acting antivirals in chronic hepatitis C. (November 2018) - Umemura, Takeji; Yamazaki, Tomoo; Joshita, Satoru; Sugiura, Ayumi; Fujimori, Naoyuki; Matsumoto, Akihiro; Ota, Masao; Tanaka, Eiji
Highlights: Serum chemokine levels are higher in chronic hepatitis C patients than in controls. Lower MIP-1β and higher RANTES levels are significantly associated with a non-SVR in DAA therapy. A combination of MIP-1β and RANTES is highly predictive of DAA treatment failure. Most chemokines decreased in patients with a SVR to DAA therapy. Abstract: Although serum chemokine levels have been reported to influence the outcome of interferon-based treatment in patients with chronic hepatitis C, their effect on the hepatitis C virus (HCV) response to direct-acting antiviral agents (DAAs), which can achieve high rates of a sustained virological response (SVR), is largely unknown. To clarify this relationship, 9 chemokines (eotaxin, GRO-α, IL-8, IP-10, MCP-1, MIP-1α, MIP-1β, RANTES, and SDF-1α) were quantified before, during, and after DAA treatment using serum samples obtained from 57 patients with chronic hepatitis C. All baseline median chemokine levels were significantly higher in patients with chronic hepatitis C than in healthy subjects ( P < 0.05). In particular, lower MIP-1β (≤71.5 pg/mL) and higher RANTES (>671.5 pg/mL) levels were significantly associated with patients who failed to clear HCV RNA ( P = 0.0039 and 0.013, respectively). Prediction of a clinical response based on a combination of these chemokines demonstrated high sensitivity (82%), specificity (85%), negative predictive value (95%), and area under the curve (0.833). The non-SVR rate (56.3%; 9 of 16) was significantly higher in patients with low MIP-1β and high RANTES compared with other combinations. Moreover, baseline MIP-1β and RANTES were both additive and independent for predicting a non-SVR. Apart from an increase in eotaxin, all chemokines became decreased in patients with a SVR. In conclusion, a combination of serum MIP-1β and RANTES levels may be predictive of a treatment response to DAAs in Japanese patients with chronic hepatitis C.